2011
DOI: 10.1016/j.biopsych.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Nicotine Reward and Reinstatement by Activation of Alpha-Type Peroxisome Proliferator-Activated Receptors

Abstract: Background-Recent findings indicate that inhibitors of fatty acid amide hydrolase (FAAH) counteract the rewarding effects of nicotine in rats. FAAH inhibition increases levels of several endogenous substances in the brain, including the endocannabinoid anandamide and the noncannabinoid fatty-acid ethanolamides oleoylethanolamide (OEA) and palmitoylethanolamide (PEA), which are ligands for alpha-type peroxisome proliferator-activated nuclear receptors (PPAR-α). Here, we evaluated whether directly-acting PPAR-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 41 publications
12
107
0
Order By: Relevance
“…Although OEA has no significant activity in the CB 1 receptors, it strongly activates peroxisome proliferator-activated receptor a (PPAR a ) signaling in vivo (Fu et al, 2003). PPAR a activation by OEA and other agonists reduces nicotine SA, prevents nicotine-induced increases in VTA DA cell burst firing, and attenuates nicotine-induced increases in NAc DA release (Mascia et al, 2010(Mascia et al, , 2011Melis et al, 2008). PPAR a receptors can exert tonic inhibition of DA cell activity, as their antagonism increases the spontaneous firing rate of VTA DA neurons (Melis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although OEA has no significant activity in the CB 1 receptors, it strongly activates peroxisome proliferator-activated receptor a (PPAR a ) signaling in vivo (Fu et al, 2003). PPAR a activation by OEA and other agonists reduces nicotine SA, prevents nicotine-induced increases in VTA DA cell burst firing, and attenuates nicotine-induced increases in NAc DA release (Mascia et al, 2010(Mascia et al, , 2011Melis et al, 2008). PPAR a receptors can exert tonic inhibition of DA cell activity, as their antagonism increases the spontaneous firing rate of VTA DA neurons (Melis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that experimental drugs that activate PPARa block nicotine-induced firing of dopamine neurons in the VTA and nicotine-induced elevations of extracellular dopamine levels in the nucleus accumbens shell of rats, and that they decrease nicotine-seeking behavior in rats and monkeys (Melis et al, 2008Scherma et al, 2008;Forget et al, 2009;Luchicchi et al, 2010;Mascia et al, 2011). These preclinical findings suggest that PPARa could be an effective target for anti-smoking medications.…”
Section: Introductionmentioning
confidence: 90%
“…Completion of each five-response fixed ratio was treated by the computer as a virtual injection of nicotine, and the rat's virtual nicotine level was calculated continuously based on a clearance half-life of 55 min. The light was only presented when the virtual nicotine level was below 202 mg/kg, the mean level (calculated using the procedure of Panlilio et al, 2003) at which rats self-administered nicotine in a previous study (Mascia et al, 2011). To assess potential interactions between nicotine and clofibrate, half the rats were treated with nicotine (0.4 mg/kg, subcutaneous, 10 min before session) and half with saline before every food self-administration session.…”
Section: Food Self-administration In Ratsmentioning
confidence: 99%
“…Nonetheless, previous anatomical, biochemical and electrophysiological studies have provided compelling evidence that the N-acylethanolamine anandamide and the endogenous ligands to peroxisome-proliferatoractivated receptor-alpha (PPARa; i.e. oleoylethanolamide, OEA; palmitoylethanolamide, PEA), as well as the endocannabinoid/vanilloid N-arachidonoyldopamine (NADA) are also present within the VTA [31,34,[38][39][40][41][42][43], thus suggesting discrete physiological roles for each endocannabinoid and cognate molecule in the modulation of DA neuron and its related behaviour.…”
Section: Endocannabinoid Systemmentioning
confidence: 99%
“…Additionally, preclinical studies strongly suggest that PPARa could be an effective target for antismoking medication [39,[41][42][43]73,111,112]. Noteworthy, being PPARa-mediated actions directed at controlling either function and/or number of b2*-nAChRs, their effects are restricted to nicotine.…”
Section: Review Endocannabinoids and Dopamine Neurons M Melis And Mmentioning
confidence: 99%